The Responsibility of Broker to The Third Party Based on Legal Sale - Salma, Radmila (Universitas Negeri Semarang, 2019)
Trading through Broker, one side is easy; the other side could be difficult. The difficulty here means determining the hidden defects responsibility and law risk of goods purchased by a third party. After further research on the existance law, the responsibility is determined by the law of the intermediary relationship with the parties involved in the transaction. Trading through agents and brokers, their legal relationship with the employer is the authority, so the agent is outside the parties doing transaction, then who shall be responsible for the third party is the businessman as a seller. While trading through distributors and commissioners, the legal relationship to the third party (the buyer) is the legal relationship where the commissioner and distributors are as sellers, they shall be responsible to the third party (the buyer) over the hidden defect and law risk of the goods he bought.